2004
DOI: 10.1897/03-414
|View full text |Cite
|
Sign up to set email alerts
|

Fate and metabolism of [15N]2,4,6‐trinitrotoluene in soil

Abstract: The fates of the labels from [14C] and [15N] trinitrotoluene were analyzed in bioreactors under aerobic conditions in soil treated by a fungal bioremediation process with Stropharia rugosoannulata and in control soil. Up to 17.5% of the 15N label had a different fate than the 14C label. Three N-mineralization processes were identified in detailed experiments with [15N]TNT. About 2% of the 15N label was found as NO3- and NH4+, showing simultaneous processes of direct TNT denitration (I) and reduction with cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Alternatively, they may point to the production of volatile N-compounds derived from the oxidative denitration of 15 N-TNT or by the biological transamination of the reduced transformation products. Such reactions were previously suspected to be in part responsible for elevated (NO 2 + NO 3 )-N concentrations observed in contaminated soils from a former ordnance plant (Comfort et al, 1995) and partly responsible for the 15 N add losses observed by Weiß et al (2004). In our study those reactions may also explain the presence of inorganic 15 N add in the leachate as it was assumed from its the low C t / 15 N add ratio and the solid-state 13 C NMR spectroscopic analysis.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Alternatively, they may point to the production of volatile N-compounds derived from the oxidative denitration of 15 N-TNT or by the biological transamination of the reduced transformation products. Such reactions were previously suspected to be in part responsible for elevated (NO 2 + NO 3 )-N concentrations observed in contaminated soils from a former ordnance plant (Comfort et al, 1995) and partly responsible for the 15 N add losses observed by Weiß et al (2004). In our study those reactions may also explain the presence of inorganic 15 N add in the leachate as it was assumed from its the low C t / 15 N add ratio and the solid-state 13 C NMR spectroscopic analysis.…”
Section: Discussionsupporting
confidence: 63%
“…Comparable decreases of recovery were recently observed during the aerobic degradation of grass material in the presence of 15 N-TNT (Knicker, 2003). Losses of up to 12% 15 N add were also detected for soils spiked with 15 N-TNT after 108 days of fungal bioremediation (Weiß et al 2004). Considering the continuity of the 15 N add -losses with increasing incubation time in the present experiment, they are not readily explainable by handling and sample preparation alone.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is usually accompanied by the production of light, heat, sound, and pressure. Nitro-aromatic and nitramine compounds, such as 2,4,6-trinitrotoluene (TNT), hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), and octahydrol-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX), are common military explosives that are found in soils at destruction ranges, explosive dumping grounds, industrial production sites, firing ranges, and ammunition factories [1][2][3]. The United States Environmental Protection Agency (USEPA) has listed Nitro-substituted explosives, including TNT and RDX, as priority pollutants, whereas RDX, classified as a potential carcinogen that is toxic to organisms, is comparatively mobile in the soil, has a low rate of degradation in soil, and presents distinct problems for bioremediation.…”
Section: Introductionmentioning
confidence: 99%
“…Release of 2,4,6-TNT to the environment represents a potential hazard because of the toxicity of 2,4,6-TNT itself, its metabolites from transformation, by-products of the manufacturing process, or incomplete combustion [1]. Furthermore, 2,4,6-TNT is a man-made substance and because of its low biodegradability it is persistent in the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%